Chemical augmentation of mitochondrial electron transport chains tunes T cell activation threshold in tumors. Issue 2 (3rd February 2022) - Dotsu, Yosuke; Muraoka, Daisuk; Ogo, Naohisa; Sonoda, Yudai; Yasui, Kiyoshi; Yamaguchi, Hiroyuki; Yagita, Hideo; Mukae, Hiroshi; Asai, Akira; Ikeda, Hiroaki
Abstract : Background: Cancer immunotherapy shows insufficient efficacy for low immunogenic tumors. Furthermore, tumors often downregulate antigen and major histocompatibility complex expression to escape recognition by T cells, resulting in insufficient T cell receptor (TCR) stimulation in the tumor microenvironment. Thus, augmenting TCR-mediated recognition of tumor antigens is a useful strategy to improve the efficacy of cancer immunotherapy. Methods: We screened 310 small molecules from our library and identified PQDN, a small molecule that activates CD8 T cells after TCR engagement, even when antigen stimulation is too weak for their activation. We used inhibitors of mitochondrial functions and Seahorse Flux Analyzer to investigate the mechanism underlying the effect of PQDN on T cells. Effect of PQDN on tumor-infiltrating CD8 T cells was examined using flow cytometry and TCR repertoire analysis. Results: PQDN increased mitochondrial reciprocal capacity through enhancement of electron transport chains (ETCs) and facilitated glycolysis via mTOR/AKT signaling, resulting in augmented CD8 T cell activation, even when antigen stimulation is extremely weak. Intratumoral administration of this compound into tumor-bearing mice tunes inactivated T cell with tumor antigen recognition potent and expanded functional T cell receptor diversity of tumor-infiltrating T cells, augmenting antitumor immune responses and retarding tumor growth. Furthermore, PQDN has a synergistic potent with T cell dependent immunotherapy, such as checkpoint inhibitory therapy or adoptive cell therapy, even in a low immunogenic tumor. We also demonstrated that this compound enhances the activation of human CD8 T cells. Conclusions: These data suggest that tuning the T cell activation threshold by chemical activation of mitochondrial ETC is a new strategy for improving therapeutic efficacy through the activation of low-avidity tumor-specific T cells.